ANALYTICAL AND NUMERICAL ANALYSIS OF TRAPPED AIR POCKET DYNAMIC RESPONSE DUE TO PRESSURE CHANGE IN LIQUID-FILLED PIPELINES - Pekolj, Jošt; Bergant, Anton; Perpar, Matjaž (Journal of Energy Technology, 2023)
This paper serves as an overview of the different approaches to modelling the filling and emptying of liquid-filled pipelines. Specifically, it compares an analytical and numerical analysis of the start-up of a liquid column in a one-dimensional pipeline with a trapped air pocket. The analytical analysis is based on the premise that there are no pressure waves travelling in the water column. For this reason, it is not suitable for pipeline systems with very small initial trapped air pockets or very high reservoir pressures. In the pipelines with parameters, as shown in this paper, the results of the analytical analysis correlate sufficiently with those of the numerical analysis.